INTERDISCIPLINARY PEDAGOGICAL WORK WITH MUSIC IN A PUBLIC SCHOOL IN RONDONÓPOLIS - Mazeto, Jhiones de Arruda; de Moraes , Francelina Fontenelle; de Jesus , Camila Aparecida Miranda; Rodrigues , Jozivane Ferreira Silva; Martins, Elkslene Ramos; Martines, Renata Galvani Garcia (Editora Impacto Científico, 2025)
This article addresses the understanding of processes related to interdisciplinary pedagogical work with music in elementary school classes at EMEB Gisélio da Nóbrega in Rondonópolis-MT, in the year 2025. The objective is to present music as an educational activity in interdisciplinary pedagogical work, highlighting that, by listening to and interpreting music, students develop critical, analytical, and reflective skills. The research was conducted through participatory practices that integrated music, playfulness, and knowledge construction. Using the song "Parabolicamará" by Gilberto Gil, the theme of globalization was explored, promoting playful interpretation, discussion, and the creation of fact sheets on advances in transportation, communication, and the circulation of information. The results indicate significant advances in the teaching and learning process in the classes involved, confirming that music contributes to expression, self-esteem, social integration, sensitivity, and cognitive development.DOI: https://doi.org/10.56238/edimpacto2025.092-048